The Main Activities Of Research And Development In Kari Related To Recent Unmanned Helicopter - Kim, D. K.; Chae, S.; Kee, Y.; Park, I. (My University, 2025)
Korea Aerospace Research Institute (KARI) has researched and developed several types of unmanned helicopter in recent period. The representative unmanned helicopters are Multi-Purpose Unmanned Helicopter which has MTOW 200kg (MPUH) and the First Korea Electric Unmanned Helicopter which has MTOW 125kg (K-EUH). The MPUH has payload 60kg, max speed 150km/h and flight time over 3hrs which had been developed during from 2017 to 2021. The K-EUH has payload 20kg, max speed 120km/h and flight time over 30min which had been developed during from 2019 to 2022. These unmanned helicopters were initiated to provide better vehicles to surveillance and delivery for military and also to provide future eco-friendly VTOL vehicle for urban parcel delivery service, urban passenger service as a part of Korea-UAM and also drone service market promotion in Korea. For the developing MPUH and K-EUH, KARI have applied the existing accumulated experiences and technologies obtained from the domestic helicopter development program. These programs are like Light Armed Helicopter (LAH), Light Civil Helicopter (LCH), Korean Helicopter Program (KHP). In Korea, there was no research and development activities on an electric unmanned helicopter with payload 20kg until 2019. The foreign electric helicopter examples such as battery and power system, electric motor for electric vehicle [1-3]. This electric helicopter has so many merits like and long flight distance, high payload, high cruise speed, resistance from wind relative to drone such as quadcopter type. From these merits, electric helicopter be able to service market like parcel delivery to the mountains, long offshore area and island [3]. After success of K-EUH technologies development, KARI can start the commercial program for the K-EUH to achieve real market. This paper describes main activities of the two major unmanned helicopter program which has been developed in KARI recently.